Associations between ALOX, COX, and CRP polymorphisms and breast cancer among Hispanic and non‐Hispanic white women: The breast cancer health disparities study. Issue 12 (22nd October 2014) - Connor, Avonne E.; Baumgartner, Richard N.; Baumgartner, Kathy B.; Pinkston, Christina M.; Boone, Stephanie D.; John, Esther M.; Mejía, Gabriela Torres‐; Hines, Lisa M.; Giuliano, Anna R.; Wolff, Roger K.; Slattery, Martha L.
<x xml:space="preserve">Abstract</x> Chronic inflammation is suggested to be associated with specific cancer sites, including breast cancer. Recent research has focused on the roles of genes involved in the leukotriene/lipoxygenase and prostaglandin/cyclooxygenase pathways in breast cancer etiology. We hypothesized that genes in ALOX/COX pathways and CRP polymorphisms would be associated with breast cancer risk and mortality in our sample of Hispanic/Native American (NA) (1430 cases, 1599 controls) and non‐Hispanic white (NHW) (2093 cases, 2610 controls) women. A total of 104 Ancestral Informative Markers was used to distinguish European and NA ancestry. The adaptive rank truncated product (ARTP) method was used to determine the significance of associations for each gene and the inflammation pathway with breast cancer risk and by NA ancestry. Overall, the pathway was associated with breast cancer risk (PARTP = 0.01). Two‐way interactions with NA ancestry (Padj < 0.05) were observed for ALOX12 (rs2292350, rs2271316) and PTGS1 (rs10306194). We observed increases in breast cancer risk in stratified analyses by tertiles of polyunsaturated fat intake for ALOX12 polymorphisms; the largest increase in risk was among women in the highest tertile with ALOX12 rs9904779CC (Odds Ratio (OR), 1.49; 95% Confidence Interval (CI) 1.14‐1.94, Padj = 0.01). In a sub‐analysis stratified by NSAIDs use, two‐way interactions with NSAIDs use were found for ALOX12 rs9904779 (Padj = 0.02), rs434473 (Padj = 0.02), and rs1126667 (Padj = 0.01); ORs for ALOX12 polymorphisms ranged from 1.55 to 1.64 among regular users. Associations were not observed with breast cancer mortality. These findings could support advances in the discovery of new pathways related to inflammation for breast cancer treatment. © 2014 Wiley Periodicals, Inc.